PENELITIAN MEKANISME STALL AKIBAT PERKEMBANGAN GELEMBUNG SEPARASI PADA SAYAP NACA 0017 SECARA EKSPERIMEN DI TEROWONGAN ANGIN SUBSONIK - Agus Aribowo (Jurnal Teknologi Dirgantara, 2004)
This paper presents the results of investigation the separation buble which growing and burst on aerofoil NACA 0017 with effect mechanism of stall in the subsonic wind tunnel. Experiment have done on wind speed 20 m per s and 30 m per s. The data pecked from the orifice of pressure with interval 2 degree until stall position. The result was separation buble which growing on the airfoil, going to ahead of airfoil together with increasing the Reynolds number. After touching, the flow appeared to separate from the upper airfoil without reattachment.